Extracto acuoso de uchuva (Physalis peruviana) : actividades antiproliferativa, apoptótica y antioxidante (2013)
ABSTRACT: Ethanolic extracts from P. peruviana showed cytotoxic activity against different cancer cell lines. Objective: To evaluate the antiproliferative activity of aqueous extract of the fruit golden berry in colon cancer cells. Materials and Methods: We analyzed cytotoxicity and selectivity index (SI) (MTT), antiproliferation (sulforhodamine-B), apoptosis (cell cycle, Annexin-V, receptors TRAIL-DR4/-DR5 and caspase-3), and antioxidant activity (content of total carotenoids and flavonoids). Results: The aqueous extract showed cytotoxic and antiproliferative effect on SW480 (IC50 = 44.2 µg/ml, SI = 11.6) and SW620 (IC50 = 85.1 µg/ml, SI = 6.0). The hypodiploid SW480 and SW620 cells increased 13% and 12% respectively as well as apoptotic SW480 and SW620 cells (19% and 21 %, respectively), expression of receptors TRAIL-DR4 /-DR5 (SW480: +59% / +53%; SW620: +67% / +65%) and activation of caspase-3. The aqueous extract scavenged OH- radicals, showed low oxygen radical capacity and low scavenging capacity for reactive oxygen and nitrogen species. The total flavonoids and carotenoids contente was 487.1 mg catechin y 0.9 mg β-carotene by 100 g powder, respectively. Conclusions: These findings suggest that golden berry may be a promising source of bioactive compounds with chemopreventive activity against human colon cancer.